Improving Narrative Writing Skills Through Video Media Utilization in Class V Students of Malaka Jaya Elementary School 07 Morning - Sari, Novy Adilla; Fahrurrozi, Fahrurrozi; Sumantri, M. Syarif (International Journal for Educational and Vocational Studies, 2019)
This study aims to improve the narrative writing skills of Class V students through the use of video media. This study is action research conducted at SDN Malaka Jaya 07 Pagi East Jakarta. The subjects of the study were Class V students, amounting to 31 students. The research was divided into two cycles (after the pre-cycle), each cycle having two and three meetings. The data analysis technique was performed by using a qualitative descriptive technique. The success of this study is seen from two criteria, namely from the observation sheet after applying video utilization and from the increasing results of narrative writing skills. The study results obtained from the use of video are to make students active in finding information and making writing and skilled at developing and utilizing their own knowledge. It is hoped that the improvement in the skills to write narration will be clearly seen in the initial cycle and increase in cycle 2 (Two). This can be seen from the initial percentage. Students who are not yet skilled or not enthusiastic/interested in writing narration by 49%, then the percentage of results in the first cycle (second meeting) is 40% and at the end of the second cycle, (third meeting) students who are not interested write only 11%. Overall at the end of the second cycle all aspects and criteria for narrative writing experienced a significant increase.